Mykola Sumtsov - a figure in the context of time - Khirina, Anna; Soshnikova, Olena (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Objective: to analyze and summarize the role and place of academician M.F. Sumtsov in the development of European and Ukrainian science and culture, to determine the peculiarities of the scientist's scientific interests, to trace the transformation of his scientific views, to analyze the contribution to the development of Ukrainian culture, the formation of the national idea, and the formation of Ukrainian national consciousness.Research methodology: the principles of analytical approach, historicism, and objectivity, embodied through the application of special-historical methods - comparative-historical, chronological, and retrospective.Scientific novelty. For the first time, materials from Fund N 1115 of the Central Rada of Ukraine CSAVO of Ukraine regarding the involvement of M.F. Sumtsov as a responsible person of the Central Rada in organizing Ukrainization of education in the Kharkiv region are introduced into scientific circulation. The biography of the scientist is supplemented with his work at the Ukrainian University in Poltava in 1918, and his arrest in 1921, made possible after studying the periodical press of the 1940s. The contribution of Sumtsov to the formation of Ukrainian studies as a separate field of scientific knowledge, to biographical and prosopographic research, the study of the nature and geography of Ukraine, the analysis of Sumtsov's correspondence in terms of his place among prominent representatives of Ukrainian culture, including S.V. Petliura, is analyzed.Conclusions. M.F. Sumtsov is a prominent figure in the history of Ukrainian and European science and culture, one of the founders of Ukrainian studies as a separate scientific field, belonged to a whole pleiad of founders of the Ukrainian national idea. Sumtsov's scientific work is characterized by interdisciplinarity, versatility, and depth of understanding of the problems of peoples' existence. The worldview, public activity, and scientific legacy of the scientist fully reflected the complex contradictions of the era from the second half of the 19th to the beginning of the 20th century. Sumtsov was a man of his time, but he went beyond its boundaries with his actions and scientific works, which remain an important source for understanding and studying the culture and spirituality of the Ukrainian people.